Time and the Entrepreneurial Journey: The Problems and Promise of Studying Entrepreneurship as a Process - McMullen, Jeffery S.; Dimov, Dimo (Journal of Management Studies, 2013)
We examine the growing disconnect between the process‐oriented conception of entrepreneurship taught in the classroom and theorized about in premier journals and the variance‐oriented conception of entrepreneurship that characterizes empirical studies of the phenomenon. We propose that a shift in inquiry from entrepreneurship as an act to entrepreneurship as a journey could facilitate process‐oriented research by initiating a dialogue about the nature of the entrepreneurial journey, when it has begun and ended, whether it might be productively subdivided into variables or events, and what if anything remains constant throughout the process. Finally, we propose that a clearer understanding of the entrepreneurial journey is necessary to distinguish the field horizontally from research on creativity and strategy, and vertically from research on more practical business functions or more abstract systems‐level concepts.